Dihalogen and Solvent-Free Preparation of syn-Bimane - Neogi, Ishita; Das, Partha J.; Grynszpan, Flavio (Synlett, 2018)
Fluorescent bimanes are low molecular weight and low toxicity molecules with applications ranging from biology to LASER dyes. The widespread use of these molecular probes has presumably been stalled by the hazards involved in their current synthetic preparation which involve handling of dangerous halogens like chlorine (gas) and bromine (liq.). The accessibility achieved by the simple and safe dihalogen and solvent-free methodologies described here open the floodgates to additional future practical applications of bimanes.
Keywords: bimane; fluorescent; monobromo-bimane; molecular economy; easy and safe synthesis